2020
DOI: 10.5020/18061230.2019.9364
|View full text |Cite
|
Sign up to set email alerts
|

Doença de Chagas: serviço de referência e epidemiologia

Abstract: Este artigo está publicado em acesso aberto (Open Access) sob a licença Creative Commons, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho seja corretamente citado. Doença de Chagas: serviço de referência e epidemiologiaChagas disease: a reference and epidemiology center Enfermedad de Chagas: servicio de referencia y epidemiologia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…In the present study, the indeterminate form was the most prevalent (44.9%). The digestive form, either isolated or associated with heart disease, had a prevalence of 11.8%, which is within the range of the mean prevalence of this clinical form (9%-41%) presented in other studies 12 - 15 , 17 , 19 , 20 , 22 . Regarding the cardiac and cardiodigestive forms, the most common cardiac stage was stage A (44.4%), which, if associated with the indeterminate form, would account for 65.8% of the cohort, with normal left ventricular systolic function on the ECG indicating patients with long-term benign prognoses.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, the indeterminate form was the most prevalent (44.9%). The digestive form, either isolated or associated with heart disease, had a prevalence of 11.8%, which is within the range of the mean prevalence of this clinical form (9%-41%) presented in other studies 12 - 15 , 17 , 19 , 20 , 22 . Regarding the cardiac and cardiodigestive forms, the most common cardiac stage was stage A (44.4%), which, if associated with the indeterminate form, would account for 65.8% of the cohort, with normal left ventricular systolic function on the ECG indicating patients with long-term benign prognoses.…”
Section: Discussionsupporting
confidence: 82%
“…Field studies performed between 1960 and the early 2000s reported a progressive increase in the mean age of patients with chronic CD over time, from less than 25 to 45 years 31 - 33 . Studies on the clinical epidemiological profile of patients with chronic CD in urban centers reported that the mean age showed the same increasing trend in the last decades, ranging from 37.7 to 67.5 years 12 , 13 , 15 , 20 - 22 . Studies conducted in nonendemic regions of the Northern Hemisphere, where patients migrated from South America, especially Bolivia and Central America, reported younger patients with chronic CD with a mean age ranging from 28.5 to 47 years 16 - 18 , 34 - 37 , reflecting the lack of CD vectorial transmission control in their countries of origin and that CD vectorial transmission remained active in rural areas.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Neste estudo, outra questão a ser considerada foi o relato dos entrevistados sobre dificuldade financeira para dar continuidade ao tratamento, visto que o CRDT ficava localizado na capital do Amapá e parte deles residia em outro munícipio ou estado. Sob esta ótica, as doenças negligenciadas refletem a dura realidade vivenciada pelas populações mais carentes, marcada pela baixa cobertura de ações preventivas, precariedade na qualidade e no acesso aos serviços de saúde, e menores chances de receber tratamentos essenciais 28 .…”
Section: Itinerário Em Busca Do Tratamento E Controle Da Doençaunclassified